The impact factors of social media users' forwarding behavior of COVID-19 vaccine topic: Based on empirical analysis of Chinese Weibo users - Sun, Kun; Wang, Han; Zhang, Jinsheng (Frontiers in Public Health, 2022)
Introduction: The forwarding behavior of social media users on posts concerned with COVID-19 vaccines topics can rapidly disseminate vaccine information in a short period, which has a significant effect on transmission and helps the public access relevant information. However, the factors of social media users' forwarding posts are still uncertain thus far. In this paper, we investigated the factors of the forwarding COVID-19 vaccines Weibo posts on Chinese social media and verified the correlation between social network characteristics, Weibo textual sentiment characteristics, as well as post forwarding. Methods: This paper used data mining, machine learning, sentiment analysis, social network analysis and regression analysis. Using "新冠疫苗 (COVID-19vaccine)" as the keyword, we used data mining to crawl 121,834 Weibo posts on Sina Weibo from January 1, 2021, to May 31, 2021. Weibo posts not closely correlated with the topic of the COVID-19 vaccines were filtered out using machine learning. In the end, 3,158 posts were used for data analysis. The proportions of positive sentiment and negative sentiment in the textual of Weibo posts were calculated through sentiment analysis. On that basis, the sentiment characteristics of Weibo posts were determined. The social network characteristics of information transmission on the COVID-19 vaccines topic were determined through social network analysis. The correlation between social network characteristics, sentiment characteristics of the text, and the forwarding volume of posts was verified through regression analysis. Results: The results suggest that there was a significant positive correlation between the degree of posting users in the social network structure and the amount of forwarding. The relationship between the closeness centrality and the forwarding volume was significantly positive. The betweenness centrality was significant positively correlated with the forwarding volume. Conclusion: According to the characteristics of users, COVID-19 vaccine posts from opinion leaders, "gatekeepers" and users with high closeness centrality are more likely to be reposted. Users with these characteristics should be valued for their important role in disseminating information about COVID-19 vaccines. In addition, the sentiment contained in the Weibo post is an important factor influencing the public to forward vaccine posts.